2016
DOI: 10.3390/cryst7010011
|View full text |Cite
|
Sign up to set email alerts
|

From Rate Measurements to Mechanistic Data for Condensed Matter Reactions: A Case Study Using the Crystallization of [Zn(OH2)6][ZnCl4]

Abstract: Abstract:The kinetics of crystallization of the R = 3 hydrate of zinc chloride, [Zn(OH 2 ) 6 ][ZnCl 4 ], is measured by time-resolved synchrotron x-ray diffraction, time-resolved neutron diffraction, and by differential scanning calorimetry. It is shown that analysis of the rate data using the classic Kolmogorov, Johnson, Mehl, Avrami (KJMA) kinetic model affords radically different rate constants for equivalent reaction conditions. Reintroducing the amount of sample measured by each method into the kinetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Most recently in 2017, a modified-KJMA (M-KJMA) 49 was proposed to ''ensure rate constants are intrinsic to the sample and reaction conditions, not the specific technique of measurement.'' 49 The assumptions behind and issues with these models are discussed elsewhere 50,51 and need not be rehashed here, save to emphasize four key points: 50,51 (i) all the models in Table 1 assume instantaneous/burst nucleation no matter if they are postulated to occur instantaneously at t = 0 or for example at some later, predetermined time, t = t 0 (known as ''sporadic'' as opposed to ''instantaneous'' nucleation in the Avrami-model literature [42][43][44][45][46][47]49 ); (ii) hence these mathematical Kolmogorov (1937), Johnson and Mehl (1939) (''KJMA''), 45,46 Erofe'ev (1946) 47 ) [a = extent (fraction) of reaction; k = a rate parameter; n = the ''Avrami exponent''] 1950 LaMer 1 Stat. mech; CNT (for S n sol formation)…”
Section: Review Materials Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently in 2017, a modified-KJMA (M-KJMA) 49 was proposed to ''ensure rate constants are intrinsic to the sample and reaction conditions, not the specific technique of measurement.'' 49 The assumptions behind and issues with these models are discussed elsewhere 50,51 and need not be rehashed here, save to emphasize four key points: 50,51 (i) all the models in Table 1 assume instantaneous/burst nucleation no matter if they are postulated to occur instantaneously at t = 0 or for example at some later, predetermined time, t = t 0 (known as ''sporadic'' as opposed to ''instantaneous'' nucleation in the Avrami-model literature [42][43][44][45][46][47]49 ); (ii) hence these mathematical Kolmogorov (1937), Johnson and Mehl (1939) (''KJMA''), 45,46 Erofe'ev (1946) 47 ) [a = extent (fraction) of reaction; k = a rate parameter; n = the ''Avrami exponent''] 1950 LaMer 1 Stat. mech; CNT (for S n sol formation)…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…[x = nucleus radius; ss = supersaturation; D = diffusion coefficient; r = (bulk) S n density; h = sphere radius] Word version: burst nucleation from supersaturated solution, then diffusion-controlled growth 2017 Martin (M-KJMA) 49 Mathematical; semi-empirical models say nothing about nucleation; instead, are really growth models post some presumed, undetailed nucleation events of unknown kinetics and unknown molecularity; (iii) the Avrami exponent, n, is a convolution of the dimension in space that the growth takes place in plus a parameter related to the assumed time dependence of the nucleation function. [42][43][44][45][46][47]49 Hence and unfortunately, the Avrami exponent parameter, n, has been destined to failure despite 480 years of literature trying to deconvolute and interpret nucleation and growth convoluted from the start into the single Avrami parameter, n. Additionally, (iv) the one k in the Avrami model is not a rate constant, as it is not defined by a balanced equation as rate constants must be.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…In our previous reports, we demonstrated that the TZT c accurately describes the temperature-dependent growth rates of diverse systems ranging from the strong SiO 2 to the fragile ortho -terphenyl (OTP). ,,, However, in none of those reports was the TZT c model directly compared to fits of data to standard models. Although it is never possible to prove a mechanistic model correct, some degree of validation is afforded to models that best fit experimental data with the fewest number of fitting parameters and for which the parameters have chemical/physical meaning, as opposed to empirical fitting parameters.…”
Section: Comparing Tztc To Standard Modelsmentioning
confidence: 99%
“… a Both Wagstaff data sets (refs and ) were used for the analysis reported here to mirror the standard model analysis in ref . Our previous TZT c analysis of SiO 2 crystallization (ref ) did not utilize data from ref because that report indicates significant oxygen deficiency of the system. b For comparison to the data analyzed in ref , growth-rate data from ref series-1 was used.…”
Section: Comparing Tztc To Standard Modelsmentioning
confidence: 99%
“…The analysis of structural transitions using diffraction or PDFs typically involves fitting data throughout the transition region with a linear combination of distinct phase models (Caliandro & Belviso, 2014;Schmidt et al, 2014;Chapman et al, 2015;Hillis et al, 2016). If there are any multi-phase regions, this linear combination approach approximates the relative volume fraction of the phases as a function of some transition coordinate (time, temperature, pressure etc.).…”
Section: Introductionmentioning
confidence: 99%